Optimizing of Human Resource Development Management through Positive Habituation at SMAK Santo Yoseph, Bali - Fatimah, Khairunnisa; Wati, Fike; Aditya, Sefia; Sartika, Dwi; Nadia, Nadia; Riana, Riana (Indonesian Journal of Social Development, 2025)
The process of character building for human resources through the application of management at SMAK Santo Yoseph in the positive habituation program is the focus of this research. This research was conducted with the aim of knowing the school management applied at SMAK Santo Yoseph in shaping the character of human resources (HR) such as teachers and students through several policies and creative programs of SMAK Santo Yoseph. The research method used is qualitative with the aim of providing a descriptive and in-depth explanation of the management of SMAK Santo Yoseph in shaping the character of students. Habitus theory proposed by Pierre Bourdieu is used in this study to analyze the positive habituation program for students at SMAK Santo Yoseph. The results of this study show that positive habituation has a good impact on teachers and students of SMAK Santo Yoseph. This research provides internal implications, namely that it can be a study material for analyzing school management for researchers. The external implication of this research is that it can be a reference material for various parties who need related information.